How should we treat postherpetic neuralgia? - Czerwik, Julia; Cieszkowska, Joanna; Dmochowska, Joanna; Czubala, Marta; Wróblewski, Wiktor (Quality in Sport, 2024)
Postherpetic neuralgia (PHN) is the most common long-term complication of varicella-zoster virus (VZV) reactivation. It is characterized primarily by persistent pain more than 90 days after the illness at the site where the rash was. This pain is sharp, burning, stabbing in nature. Postherpetic neuralgia can lead to a reduced quality of life and negatively affect sleep and daily functioning. The first line of treatment is currently conservative methods, which include anticonvulsants, antidepressants, topical lidocaine, as well as opioids and topical capsaicin. If these measures are ineffective, individually tailored interventional methods may be necessary. Among these, botulinum toxin A injection is the most common. Other methods focus on neuromodulation (which is the alteration of nerve activity through targeted delivery of a stimulus) or blocking individual elements of the nervous system.